The Relationship Between Transport Infrastructure and Urban Land Prices: A Study in Hanoi, Vietnam - Nguyen Tran Tuan; Nguyen Thanh Lan (SAGE Open)
The research topic related to transport infrastructure and the impact of increasing land prices has attracted the attention and research interest of many scholars, practitioners, and policymakers. This is an essential basis to provide the necessary information in allocating and regulating the land value-added accordingly. The study surveyed three suburban districts of Hanoi’s capital, with 524 survey samples. The case study focuses on a road project that is constructed and passes through three of Hanoi’s suburban areas. We collected these samples using the convenience sampling method. The authors chose to conduct a survey among households with land and real estate within a 1 km radius. The purpose of these survey samples is to gauge how the development of transportation infrastructure affects the cost of urban land. Additionally, the study put out seven hypotheses, and the findings indicated that, in line with the authors’ expectations, five of the seven hypotheses were supported. Specifically, land use change and accessibility are the two variables that had the strongest impact on land price changes in the study area, while travel time and development opportunities do not show any influence on land prices. The study’s findings further support the idea that the development of transportation infrastructure in urban periphery has altered the character of land use. The study also provides some policy implications in land price management to regulate and mobilize financial resources from land generated by infrastructure development.